Our Cultural Events (2008)
EAFIT Children's University held five cultural events during the year: Ethel Gilmour for young and old; Concerts Written in the stars, by Pep López from Spain and Zapatanga from Tinguiritas de Argentina; Save yourself who can, Puppet show by Titeres 4caminos by the OIXQUE group from Catalonia, Spain; Launch of the Children's University website: Going Around the Campus; and "MOMO ', a free adaptation by Momo Circus Corporation of the novel written by Michael Ende.